(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The research looked at the effects and obstacles that female instructors face in carrying out their responsibilities. Female instructors are the most tardy, absent from school, fall behind on syllabus covering, and seldom fulfill deadlines, all of which contribute to poor productivity in their teaching obligations. The goal of the study was to see how women teachers could contribute to the development of their families, to analyze the challenges women teachers face in balancing work and family responsibilities, and to suggest what steps should be taken to improve women teachers’ performance in their profession. The research discovered that women’s participation in economic activity had a number of positive effects on the family’s financial situation. The findings also found that in low-income households, both husbands and women contribute to the family income, making the family less likely to be poor. The survey also revealed that, despite women’s teachers’ important contribution to the family’s overall development, the majority of women teachers had challenges reconciling their roles as mothers and instructors, particularly when they are required to work longer hours than usual. As a result, the majority of women experience psychological stress when they are unable to accomplish a job within a certain time frame. The current research also indicates the need of a family-friendly policy and its implementation to assist women teachers who make substantial contributions to their families, communities, and nation.